2014
DOI: 10.4067/s0718-95162014005000018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vermicompost tea on yield and nitrate reductase enzyme activity in saladette tomato

Abstract: In conventional agriculture, heavy doses of chemical fertilizers and pesticides are often used to improve the yield of various horticultural crops. These chemical fertilizers and pesticides cause health problems among consumers. Due to the adverse effects of chemical fertilizers, there is interest in the use of organic fertilizers. It has long been recognized that the rate-limiting step for nitrogen assimilation, the reduction of NO 3 -to NO 2 -catalyzed by nitrate reductase (NR), is highly regulated. An incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…The lower yield, weight and size of organic produce compared to inorganically produced cucumbers could be attributed to the low nutrient concentration of organic fertilizer solutions (Márquez et al, 2014), as well to the imbalanced nutrient ratio in the compost and vermicompost teas supplied. Low nutrient concentration in organic solutions resulted from the solutions dilution in order to avoid phytotoxicity in plants (Gutiérrez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower yield, weight and size of organic produce compared to inorganically produced cucumbers could be attributed to the low nutrient concentration of organic fertilizer solutions (Márquez et al, 2014), as well to the imbalanced nutrient ratio in the compost and vermicompost teas supplied. Low nutrient concentration in organic solutions resulted from the solutions dilution in order to avoid phytotoxicity in plants (Gutiérrez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Low nutrient concentration in organic solutions resulted from the solutions dilution in order to avoid phytotoxicity in plants (Gutiérrez et al, 2008). Moreover, Preciado et al (2011) andMárquez et al (2014). reported that not only the low nutrient concentration but also the imbalanced nutrient ratio in the nutrient solutions affect the normal plant growth; thereby regularly result in a lower size and weight of fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Although several researchers have studied the effect of VCL on some crops (Ansari 2008;Carlos et al 2008;Nath and Singh 2009;Singh et al 2010;Gutiérrez-Miceli et al 2011;Leon-Anzueto et al 2011;Pant et al 2011;Arthur et al 2012;Nath and Singh 2012;Rajan and Murugesan 2012;Abduli et al 2013;Ayyobi et al 2013;More et al 2013;Rekha et al 2013;Allahyari et al 2014;Ayyobi et al 2014;Marquez-Quiroz et al 2014;Avila-Juarez et al 2015), our study is the first to evaluate VCL as a nutrient source for Stevia. Overall, the morphological attributes of Stevia such as plant height, leaf area, shoot and root fresh and dry weight were higher after 30, 45 and 60 days, in the combined application of VCL and inorganic fertilizer containing F 7 , F 8 and F 9 treatments compared with inorganic fertilizer or VCL, separately (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Govindarajan and Prabakaran (2012) have also reported the potent antimicrobial activity of vermiwash. Greenhouse and field investigations have been achieved in terms of the effects of VCL on French dwarf bean (Ayyobi et al 2014), peppermint (Ayyobi et al 2013), maize (Carlos et al 2008;More et al 2013), kharif crops (Nath and Singh 2012), tomato (Arthur et al 2012;Allahyari et al 2014;Marquez-Quiroz et al 2014), pak choi (Brassica rapa Cv Bonsai, Chinensis group) (Pant et al 2011), lemongrass (Leon-Anzueto et al 2011, black gram (Rekha et al 2013) spinach, onion, potato (Ansari 2008), certain summer vegetable crops (Nath and Singh 2009), mango (Sathe and Patil 2014), cow pea and rice (Rajan and Murugesan 2012). Most of these studies confirmed that VCL positively influenced plant yield and quality, resulting in enhanced crop production.…”
Section: Introductionmentioning
confidence: 99%
“…However, these chemicals cause health problems among consumers (Larios et al, 2011;Márquez-Quiroz et al, 2014) and to the environment, as in areas where these substances are applied, the leached water draws nitrates, that pollute aquifers and springs in avocado producing regions (Tapia et al, 2012). In this sense, it has been reported that higher concentrations than10 mg L -1 of N-NO3 in drinking water can cause serious diseases in humans and young animals (Killpack and Bucholz, 1993); the nitrogen loss in avocado orchards increases during the raining season, July and October, and they pollute the environment as the leachatecarries out the nutrients.…”
Section: Introductionmentioning
confidence: 99%